Increased anxiety in offspring reared by circadian Clock mutant mice. - Hiroko Koizumi (Public Library of Science (PLoS), 2013)
The maternal care that offspring receive from their mothers early in life influences the offspring's development of emotional behavior in adulthood. Here we found that offspring reared by circadian clock-impaired mice show elevated anxiety-related behavior. Clock mutant mice harboring a mutation in Clock, a key component of the molecular circadian clock, display altered daily patterns of nursing behavior that is fragmented during the light period, instead of long bouts of nursing behavior in wild-type mice. Adult wild-type offspring fostered by Clock mutant mice exhibit increased anxiety-related behavior. This is coupled with reduced levels of brain serotonin at postnatal day 14, whose homeostasis during the early postnatal period is critical for normal emotional behavior in adulthood. Together, disruption of the circadian clock in mothers has an adverse impact on establishing normal anxiety levels in offspring, which may increase their risk of developing anxiety disorders.